ORGANIZATIONAL CULTURE, COMPENSATION, AND WORK MOTIVATION HAVE A SIGNIFICANT INFLUENCE ON TURNOVER INTENTION - Desi Susanti; Anik Herminingsih (Dinasti International Journal of Education Management And Social Science, 2021)
This study aims to analyze the influence of organizational culture, compensation, and work motivation on turnover intention. This study involved 112 permanent employees at PT Sinergy Information Pratama, and data were collected by giving questionnaires to permanent employees that had been sampled in the study. Data analysis used multiple linear regression analysis with the help of Statistical Package for the Social Sciences version 24 program. The test results of the research instrument were said to be valid and reliable. The results also show that organizational culture has a negative and significant effect on turnover intention, compensation has a negative and significant effect on turnover intention, and work motivation has a negative and significant effect on turnover intention. Therefore, it can be concluded that when organizational culture, compensation, and work motivation decrease, turnover intention will increase and vise versa.